Human capital as a location factor : arguments for the education policy discussion from a labour market policy standpoint - Buttler, Friedrich [Verfasser]; Tessaring, Manfred [Verfasser] (My University, 1994)
"Human capital is one of the central strategic components for the location of production facilities in Germany. Human capital, however, can only be formed and maintained by qualified basic education, vocational training and further training. The best possible and continous qualifications are necessary and advantageous for the individual as well. Unskilled persons are subject to the greatest job risks and often find inadequate job opportunities. The number of jobs for this group of persons will continue to decrease. Business and the public sector will need even higher qualifications at all levels in the next few decades, if the Federal Republic of Germany is to hold up to internationale competition. Therefore, the appeal of the dual system of vocational training and of succeeding further training must be enhanced and the conditions for studying at university improved. However, although active qualification and further training policies are necessary, they are by no means sufficient for managing structural change. Other policy areas and the hole system itself will still be called upon to make their contributions on the process." (author's abstract, IAB-Doku) ((en)) Die Autoren heben die Bedeutung des Humankapitals als Standortfaktor für die Bundesrepublik Deutschland hervor und plädieren - auch aus arbeitsmarktpolitischer Sicht - für eine weitere Intensivierung der beruflichen Aus- und Weiterbildung. (IAB)
Humankapital als Standortfaktor : Argumente für die bildungspolitische Diskussion aus Sicht der Arbeitsmarktpolitik
Keywords: S 4.3.6 Human Capital; S 2.3 Berufsbildungspolitik; S 1.3.1 Ausbildung im Dualen System; Standortfaktoren; Humankapital; Bildungspolitik; Duales System; Berufliche Weiterbildung; Quantitative Angaben